Hidden symbols: How informal symbolism in digital interfaces disrupts usability for preschoolers. Issue 90 (June 2016) - Hiniker, Alexis; Sobel, Kiley; Hong, Sungsoo (Ray); Suh, Hyewon; Irish, India; Kientz, Julie A.
Abstract: Linking a symbol to the object it represents is a skill that develops gradually over the first few years of life. However, prior work shows that frequent use of this capacity makes it unintuitive for adults to recognize it as a challenge for young children. We hypothesized that this disconnect would manifest in software interfaces designed for young children, such that applications would embed symbols that the target audience would fail to understand. We conducted a randomized controlled trial with 34 preschoolers between the ages of 2 and 5 to assess their ability to work with user interface elements that require symbolic mappings. In particular, we assessed, (1) symbolic progress bars and (2) demonstrations of touch interactions by an on-screen cartoon hand. We found that these techniques are entirely inaccessible for children under 3 and that they require specific design choices to facilitate understanding in children between the ages of 3 and 5. Among a sample of 94 popular apps targeting children in this age range, we found that these symbolic techniques are incorporated into 44% of apps for preschoolers. We further found that embellishing symbolic elements with visual detail, a common practice in apps for preschoolers, increases children׳s cognitive burden and is an additional barrier to performing the symbolic mappings necessary to use these interfaces. We present design alternatives that make these prevalent user interface elements accessible to this user group. Graphical abstract: